Teaching social work in an era of New Public Management: Encouraging emotion, critical reflection, and collectivity as tools of resistance - Carlton, Rosemary; MacDonald, Sue-Ann (Intervention)

(untitled) (Ordre des travailleurs sociaux et des thérapeutes conjugaux et familiaux du Québec (OTSTCFQ), 2021)
Educating the next generation of social workers to practice in accordance with the values of the discipline is increasingly complicated in an era of practice shaped by neoliberalism and systems of New Public Management. Based on data drawn from collaborative autoethnographic conversations between two social work educators, this article responds to a sense of disillusionment, anxiety and powerlessness associated with entering today’s field of practice, as witnessed in their classrooms. Located at the intersection of two areas of scholarship – one stressing the importance of accompanying students in developing abilities to attend to emotion in social work practice with vulnerable, marginalised populations and, the other, identifying social work education as a potential site of resistance against the devaluing of social work evident in systems influenced by prevailing neoliberal attitudes – this article proposes considering emotion in the classroom as a means of confronting students’ (and educators’) feelings of disenchantment  and powerlessness and inspiring hope for the (re)establishment of social work values in contemporary practice.